(untitled) (New York, 2007)
Coverage of global markets, new technologies, and multiculturalism throughout make this dynamic text the cutting-edge choice for public relations courses. Accompanied by a unique, free DVD with video interviews of leaders in the public relations field, the text presents and explains in a personal, jargon-free style the fundamental tools of public relations practice, providing a multi-disciplinary understanding of the emerging trends within the field
Keywords: Public relations,Public relations,Quan hệ công chúng,Quan hệ công chúng; United States,Hoa Kỳ